Дискусійні питання історії ЗУНР - Кондратюк, К. (Україна: культурна спадщина, національна свідомість, державність, 2009)
У статті аналізуються питання, які все ще залишаються в історіографії Західноукраїнської Народної Республіки. Автор звертає увагу на контроверсійні точки зору щодо революційних подій, які відбулися 1 листопада 1918 р. у Львові, стосовно часу існування ЗУНР, Акту злуки УНР та ЗУНР, причин поразки Української Галицької армії тощо. The author of the article analyses the questions that are still disputable in modern
Ukrainian historiography. The author attracts our attention to the controversial points
of view concerning the type of revolutionary events which took place on the 1 st of
November 1918 in Lviv, concerning the time of WUPR existence, concerning the Act of
Unification of Western Ukrainian People’s Republic end Ukrainian People’s Republic ,
concerning the reasons of the defeat of Ukrainian army, etc.